Effects of high‐intensity physical training on muscle fiber characteristics in poststroke patients. Issue 5 (9th May 2017) - Andersen, Jesper L.; Jørgensen, Jørgen R.; Zeeman, Peter; Bech‐Pedersen, Daniel T.; Sørensen, Jane; Ara, Ignacio; Andersen, Lars L.
ABSTRACT: Introduction: Stroke is a leading cause of disability worldwide. High‐intensity physical training can improve muscle strength and gait speed, but adaptive mechanisms at the muscle cellular level are largely unknown. Methods: Outpatients with poststroke hemiparesis participated in a 3‐month rehabilitation program combining high‐intensity strength and body‐weight supported treadmill‐training. Biopsies sampled bilaterally from vastus lateralis muscles, before, after, and at 1‐year follow‐up after intervention, were analyzed for fiber size, type, and capillarization. Results: At baseline, paretic lower limbs had smaller muscle fiber size and lower type I and IIA and higher type IIX percentages than nonparetic lower limbs. Paretic lower limbs had increased type IIA fibers after training. At follow‐up, no difference between the lower limbs remained. Conclusions: Although high‐intensity training appeared not to induce changes in fiber size or capillarization, increased type IIA fiber percentages may contribute to muscle power and endurance, which is crucial for functional capacity. Muscle Nerve 56 : 954–962, 2017